STAGES OF DESIGNING A SYSTEM OF MATHEMATICS VIDEOLESSONS: THE ADDIE MODEL - Baryshok, Maryna; Termenzhy, Daria (Physical and Mathematical Education, 2021)
The authors’ experience of designing mathematics videolessons according to the ADDIE model of the instructional design theory is given in the paper. All five stages of designing process are described in detail: analysis, designing, development, implementation and evaluation. The main tasks to be solved by the developer at each of these stages are pointed out. The feasible formats of video recording are proposed by authors (on basis of analysis of existing videolessons). Formulation of the problem. In modern reality, one of the appropriate ways of implementation of multimedia technologies is using of videolessons in teaching practice. The applying of educational videos would provide students the opportunity of self-paced study in their own time and schedule, mastering their knowledge and skills, focusing on their own understanding, rather than the pace of the majority of the group.Materials and methods. Both theoretical and empirical methods were used in this research. These methods are: the analysis of existing research papers for choosing the model theory of creating and using educational videos; modeling of pedagogical processes to assess the possibility of using video lessons in teaching mathematics; identification of criteria for evaluating the effectiveness of the designed system of videolessons; survey to identify some ways for improving of developed video materials.Results. After five years long study of designing educational videos, a system of videolessons has been created and introduced into the educational process. The system consists of 25 videos of the "Functions" content line for students of 7-11 grades. Some samples of the authors’ videolessons are given in the article.Conclusions. Implementation of the developed videos into teaching practice was carried out on the basis of the Faculty of Mathematics and Information Technologies (now the Faculty of Information and Applied Technologies) of Vasyl Stus Donetsk National University and Oleksandr Pushkin gymnasium №153. It was found that the implementation of the described requirements for the development and using of video lessons for secondary school students would improve the quality of mathematical competence of students in algebra, and also would impact personal development, in particular, motivation.
Keywords: multimedia lessons; educational videos; ADDIE model; STEAM-education; teaching mathematics; content line